2021
DOI: 10.1097/shk.0000000000001875
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effect of Resuscitative Endovascular Balloon Occlusion of the Aorta in Hemodynamic Instability Secondary to Acute Cardiac Tamponade in a Porcine Model

Abstract: Background: The pre-hospital use of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) is increasing, although it remains controversial, in part because of suggested contraindications such as acute cardiac tamponade (ACT). As both the pre-hospital and in-hospital use of REBOA might potentially occur with concurrent ACT, knowledge of the hemodynamic effect of REBOA in this setting is crucial. This study, therefore, aimed at investigating the physiological effects of REBOA in hemodynamic instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In contrast to the previous Delphi study, it was now agreed that patients in extremis are REBOA-candidates when cardiac tamponade is ruled out. Interestingly, in a porcine model of shock due to acute cardiac tamponade, McGreevy et al 43 demonstrated significant increases in SBP and carotid blood flow with no change in cardiac output and prolonged survival rates. Resuscitative endovascular balloon occlusion of the aorta might therefore even be considered in the presence of nonexcluded cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous Delphi study, it was now agreed that patients in extremis are REBOA-candidates when cardiac tamponade is ruled out. Interestingly, in a porcine model of shock due to acute cardiac tamponade, McGreevy et al 43 demonstrated significant increases in SBP and carotid blood flow with no change in cardiac output and prolonged survival rates. Resuscitative endovascular balloon occlusion of the aorta might therefore even be considered in the presence of nonexcluded cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%